(untitled) (Global Journal of Science Frontier Research, 2019)
In the present work, Cu doped ZnO thin films were deposited on Indium Tin Oxide (ITO) substrates using Pulse Laser Deposition(PLD) at different substrate temperatures. The effect of substrate temperature on the structure of thin films, surface morphology, optical, and electrical properties of the deposited thin films was investigated. The structure of Cu doped ZnO confirmed by using a X-ray diffraction pattern. X-ray diffraction patterns show that all thin films have a wurtzite structure with (002) orientation. Atomic force microscopy are used for surface analyses. The transmittance of the thin films was measured in the wavelength range of 300 nm -800 nm. The band gap of the thin films was estimated (3.14 eV to 3.28 eV) using the UV-Visible absorption spectra. Raman spectroscopy was used to find the atomic bond behavior at room temperature and lower than room temperature. These films have a possible application in thin films based on solar cells and sensors.